2021
DOI: 10.1016/j.ecns.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low-fidelity Simulation-based Experiences in a Pharmacology Classroom Setting in Prelicensure Graduate Nursing Education

Abstract: Background: Simulation in a pharmacology nursing class has positive outcomes related to knowledge and confidence in undergraduate nursing education. The purpose of this study is to explore the use of simulation on knowledge, confidence, and competence in a prelicensure graduate pharmacology class. Sample: A convenience sample was comprised of graduate prelicensure nursing students (N ¼ 44) enrolled in a nursing pharmacology course. The sample was divided into an experimental (n ¼ 21) and control (n ¼ 23) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…Our study shows that very positive results were obtained from using simulation as a means of teaching professional skills such as the safe administration of nursing medication, a finding that corroborates previous research in this field [ 18 , 26 30 , 43 ]. In general, better results were obtained for the six rights during the simulation than in the prior questionnaire.…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows that very positive results were obtained from using simulation as a means of teaching professional skills such as the safe administration of nursing medication, a finding that corroborates previous research in this field [ 18 , 26 30 , 43 ]. In general, better results were obtained for the six rights during the simulation than in the prior questionnaire.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of significantly improved knowledge in the LFS group at the posttest are consistent with findings from the previous studies as in the study by Brauneis et al, 24 who conducted a quasi-experimental comparison group pretest/posttest research study and found that the experimental group had a statistically significant difference in pharmacology knowledge at posttest than pretest after using low-fidelity simulation. Moreover, another quasi-experimental study including 172 randomly chosen nurses using low-fidelity simulation training supported the results of the current study conducted by Angelina et al, 25 which aimed to assess the effectiveness of a low-fidelity simulation-based training intervention in enhancing knowledge of nurses on management of labor.…”
Section: Discussionsupporting
confidence: 90%
“…The responses align with the literature, which suggests simulation can be a useful, fun method of reinforcing learning, fostering confidence, and engaging students in the learning process. 2,3…”
Section: Creative Interactive Learning Experiencementioning
confidence: 99%
“…The student-created and role-played classroom simulation builds on previous knowledge, is student-focused, and actively engages both participants and observers. The literature discusses the benefits of using simulation in the classroom to improve understanding of content and build student confidence 2,3. Babla et al 3.…”
mentioning
confidence: 99%